Avitono (2020)
The Birdlife reception, rehabilitation and birdwatching center, seeks to conserve, protect and highlight the ecological wealth and importance of the Tibabuyes wetland. Taking into account that Bogota is the capital city of the world with the highest number of bird species inhabiting its diverse ecosystems, the Tibabuyes wetland has a great biological potential since it is located in an IBA area (Important Bird and Biodiversity Areas). Even though, the territory that surrounds the wetland has alienated itself from it and has conceived the wetland as a barrier for urban development. This is why the project itself seeks to be a sensitive transition between the urban world and the wetland, between man and bird. This is possible through the implementation of ecological education as the basis for the conservation of the ecosystem?s birdlife. It also focuses on nature tourism (primarily bird watching) and on the development of an architecture and public space that gradually connects the inhabitants and visitors of the place with the wetland and the biodiversity that lives within its boundaries. The project, AVITONO, seeks to be the ecotone, or transition zone between two worlds that are dichotomous to the naked eye.